Hierarchical mesoporous graphene@Ni-Co-S arrays on nickel foam for high-performance supercapacitors. (10th April 2015) - Nguyen, Van Hoa; Lamiel, Charmaine; Shim, Jae-Jin
Graphical abstract: Highlights: Hierarchical mesoporous graphene@Ni-Co-S arays have been decorated on Ni foam. The electrode exhibits a high specific capacitance of 9.2 F cm −1 at 100 mA cm −1 . The electrode presents large electroactive surface area and excellent structural stability. Abstract: Hierarchical mesoporous graphene and ternary nickel cobalt sulfide (Ni-Co-S) arrays on nickel foam were designed and fabricated by chemical vapor deposition and electrodeposition for supercapacitor applications. The electrodes exhibited rapid electron and ion transport, large electroactive surface area, and excellent structural stability owing to the highly conductive, mesoporous nature of graphene and the Ni-Co-S nanosheets, as well as to the open framework of the three-dimensional nanoarchitectures. The specific capacitance of the obtained electrode was as high as 9.2 F cm −1 at a high current density of 100 mA cm −1, indicating promising applications as an efficient electrode for electrochemical capacitors.